Diagnóstico y alternativas al sistema de gestión de residuos sólidos en dos parroquias del cantón Quilanga pertenecientes a la parte alta de la Cuenca Catamayo. - Elizalde Granda, Mayra Gabriela (2019)
The purpose of this research is to carry out a diagnosis of the solid waste management system in Fundochamba, a parish located in Quilanga; for this purpose, the composition and percentage of household, commercial and special solid waste production in the studied areas based on the quartering method in which the generation per capita, density, and volume was obtained. Similarly, the main problems in solid waste management were determined through interviews with the head of the Management, Protection and Environment Department of the Municipality in Quilanga (GAD in Spanish), and the President of the local government in Fundochamba, as well as surveys to the residents, a checklist to determine the operating status of the landfill in Quilanga, and a diagnosis of the studied areas. Finally, alternatives were presented for an adequate management and final disposal of solid waste based on the Zero Waste indexes proposed. In both places, the urban area of Quilanga and the rural area in Fundochamba, the most significant problems are the inadequate final disposal of solid waste, leachate drainage treatment is not executed, waste entering the landfill is not weighed. In Quilanga the Per Capita Generation is 0.33 kg/hab/day, and 47.43 kg/day of solid waste is generated, of which 18.33 kg/day corresponds to inorganic and 29.10 kg/day to organic. In Fundochamba the Per Capita Generation is 0.27 kg/hab* day, and 34.29 kg/day of solid waste is generated, of which 16.09 kg/day corresponds to inorganic and 18.21 kg/day to organic. The alternatives presented are aimed to improve solid waste management through the following programs: environmental education, efficient use of solid waste (organic and inorganic), industrial safety and professional health, enhancement of the collection service, upgrading and providing equipment to the landfill located in Quilanga. Keywords: Per capita generation, Management, Waste